On-gift system - Nur Syazwani, Zaifulbahari (2018)
Distant distances are one of the things that are often to be a major problem for people, especially for children or those who are studying and working away from family and home. This has made it difficult for them to celebrate and give gifts to their loved ones on certain special occasion. Although there are various systems that offer online purchases, however, even if it sent to the intended person, there is no privilege can be felt. Therefore, the On-Gift system is developed to help the public in choosing and purchasing gifts easily online. In this system, users need to choose the location of the purchase and so they have to choose the type of gift they want to buy. The system also offers delivery services to addresses set by users. Therefore, users are required to share some personal information such as names and addresses into the system so that it will facilitates the company to obtain users’ data. The objective of this system is to create a web-based system that can help customers to buy and give gifts to loved ones even in long-distance situations. Rapid Application Development (RAD) is a method used to develop this system. There are four levels in RAD, the first stage is requirement planning stage, the second is the user design stage, while the third is the stage of rapid construction and the latter is the transition stage.